Pulmonary Function Tests in Transport Workers Within the Ring Road of Kathmandu Valley - Ghimire, Dayaram; Manna, Saurav; Shrestha, Esha (Med Phoenix, 2018)
Background: Transport workers (drivers and helpers) are exposed to dust and vehicle emissions continuously throughout their duty hours. Most common health hazards on exposure to air pollution is related to respiratory system. The main objective of the study was to measure lung function parameters of transport workers and compare results with those of the general public. This study also aimed to evaluate the effect of job duration on transport workers. Methods: A cross-sectional comparative study was done in a total of 78 apparently healthy, non-smoking, male transport workers working for at least one year within the Ring Road in Kathmandu valley. The results obtained from these professionals were compared to 78 apparently healthy, non-smoker male general public, working as students in medical college and administrative staff in transport office. Results: Statistically significant decrease in Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), Peak Expiratory Flow Rate (PEFR) and Forced Expiratory Flow between 25% and 75% (FEF25%-75%) among transport workers was noted as compared to the general public. Transport workers working for more than five years also have deteriorated above mentioned parameters as compared to their colleagues working five years or less in the same profession. Conclusions: This study concludes that there is an adverse effect of ambient air pollution on pulmonary functions of the transport workers. The findings of this study also demonstrate that the transport workers working in Kathmandu valley for more than five years have deteriorated pulmonary functions. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 52-59